Analisis dan Desain Sistem Pakar Sebagai Pendiagnosa Gangguan Hati - Saragih, Agus Sehatman (Universitas Palangka Raya, 2014)
Liver has a very important rolefor the human body, especially as an antidote tothe humanbody. Liver disordercan becategorized intoseveraltypes. The ability ofexperts/physiciansindiagnosingliver disordersis notalwaysoptimal. This was caused bythe amount ofinformationthatmust beprocessedandthe similarityof symptomsinliverdisorders.Expert systemsfor the diagnosis liverdisordersis expected to helpmedicalexpertsinstoringandprocessing informationfor initial diagnosis of liver disorder. CertaintyFactor(CF)Methodscandescribe the level ofconfidenceof expertstodiagnosethe type ofliverdisorder.Developmentphasesof expert systemsincludesinformationanalysis, functionalitysystemanalysis, use cases, activitydiagrams, data flow diagram(DFD), databasedesignandinterfacedesign.